STRUCTURAL AND DOCKING STUDIES ON (2R, 3R)-2-AZANIUMYL-3-HYDROXYBUTANOATE METAL COMPLEXES (International Journal of Food and Nutritional Sciences, 2022)
Chemistry gives the collective behaviour of atoms in molecule, and varies accordingly with the presence of elements, form metal to non-metals. Amino acids and metal ions are the key components of life. This work is the study of blending metal ions of II A & B, Be, Mg and Zn as sulpahtes and L-threonine through the computational studies. The surfaces were obtained by Crystal Explorer/DFT/B3LYP/631G**. Computations were done through Firefly/B3LYP method using 6-31G** basis set. All the calculations were performed at 25 °C in gas phase. It was observed that hydroxyl group has poor binding ability due to the covalently and strongly held hydrogen. The metal ion stabilises the ligand in the metal complexes and metal ion can act as drug carrier. In docking the complexes have H-bond, hydrophobic, π-stacking and complex formation interaction with the proteins. It was concluded that chemistry is the chemistry of hydrogen